2011
DOI: 10.1007/s10571-011-9736-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Parameters in Urine from Patients with Disorders of Propionate Metabolism: a Beneficial Effect of l-Carnitine Supplementation

Abstract: Propionic (PA) and methylmalonic (MMA) acidurias are inherited disorders caused by deficiency of propionyl-CoA carboxylase and methylmalonyl-CoA mutase, respectively. Affected patients present acute metabolic crises in the neonatal period and long-term neurological deficits. Treatments of these diseases include a protein restricted diet and L: -carnitine supplementation. L: -Carnitine is widely used in the therapy of these diseases to prevent secondary L: -carnitine deficiency and promote detoxification, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 39 publications
2
42
1
2
Order By: Relevance
“…Antioxidants may guard against ROS toxicities by the prevention of ROS construction, by disruption of ROS attack, scavenging reactive metabolites and converting them to less reactive molecules or by enhancing the resistance of sensitive biological target to ROS attack (Siddique et al, 2010) and oxidative stress L-Carnitine is a vitamins like substance found in different food items and it is derived from lysine and methionine, is a substance essential for the oxidation of long-chain fatty acids in the mitochondria and protection of cell membranes from damage caused by free oxygen radicals (Peivandi et al, 2010). Antioxidant properties have also been documented for L-Carnitine such as prevention of lipid, protein, and DNA damage, as well as increase of non-enzymatic and enzymatic antioxidant levels (Derin et al, 2004;Ribas et al, 2010), in addition, L-Carnitine is able to act as a metal chelator, scavenger of oxygen reactive species (Solarska et al, 2010;Ribas et al, 2012). L-carnitine has a cardio protective effect which is attributed to stimulating the antioxidant capacity of cardiac tissues (Mansour, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants may guard against ROS toxicities by the prevention of ROS construction, by disruption of ROS attack, scavenging reactive metabolites and converting them to less reactive molecules or by enhancing the resistance of sensitive biological target to ROS attack (Siddique et al, 2010) and oxidative stress L-Carnitine is a vitamins like substance found in different food items and it is derived from lysine and methionine, is a substance essential for the oxidation of long-chain fatty acids in the mitochondria and protection of cell membranes from damage caused by free oxygen radicals (Peivandi et al, 2010). Antioxidant properties have also been documented for L-Carnitine such as prevention of lipid, protein, and DNA damage, as well as increase of non-enzymatic and enzymatic antioxidant levels (Derin et al, 2004;Ribas et al, 2010), in addition, L-Carnitine is able to act as a metal chelator, scavenger of oxygen reactive species (Solarska et al, 2010;Ribas et al, 2012). L-carnitine has a cardio protective effect which is attributed to stimulating the antioxidant capacity of cardiac tissues (Mansour, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The antiperoxidative effect of L-carnitine (LC) on different tissues has been proposed (10,11). LC protects tissues with some mechanisms against peroxidative stress; LC prevents ROS formation generated by the xanthine/xanthine oxidase system and reduces possible damage in the cell membrane (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…LC protects tissues with some mechanisms against peroxidative stress; LC prevents ROS formation generated by the xanthine/xanthine oxidase system and reduces possible damage in the cell membrane (12,13). In addition, LC has been reported to have a scavenging effect on ROS and a stabilizing impact on damaged cell membranes (13).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the physiological roles in intermediary metabolism, LC has also been found to possess antioxidant properties, such as prevention of DNA damages and increase of non-enzymatic and enzymatic antioxidant levels (Ribas et al, 2012;Derin et al, 2004). LC also raises the activities of blood antioxidant enzymes and total antioxidant capacity in a concentration-dependent manner (Cao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ALC supplementation has been reported to reduce the progression of Alzheimer's disease (Gavrilova et al, 2011;Pettegrew, McClure 2002). Patients with intermittent claudication exhibited improved walking capacity after the administration of PLC (Brevetti et al, 1995).Apart from the physiological roles in intermediary metabolism, LC has also been found to possess antioxidant properties, such as prevention of DNA damages and increase of non-enzymatic and enzymatic antioxidant levels (Ribas et al, 2012; Derin et al, 2004). LC also raises the activities of blood antioxidant enzymes and total antioxidant capacity in a concentration-dependent manner (Cao et al, 2011).…”
mentioning
confidence: 99%